In vivo pharmacological activity and biodistribution of S-nitrosophytochelatins after intravenous and intranasal administration in mice - Heikal, Lamia (Nitric Oxide, 2016)
S-nitrosophytochelatins (SNOPCs) are novel analogues of S-nitrosoglutathione (GSNO) with the advantage of carrying varying ratios of S-nitrosothiol (SNO) moieties per molecule. Our aim was to investigate the in vivo pharmacological potency and biodistribution of these new GSNO analogues after intravenous (i.v.) and intranasal (i.n.) administration in mice. SNOPCs with either two or six SNO groups and GSNO were synthesized and characterized for purity. Compounds were administered i.v. or i.n. at 1 μmol NO/kg body weight to CD-1 mice. Blood pressure was measured and biodistribution studies of total nitrate and nitrite species (NOx) and phytochelatins were performed after i.v. administration. At equivalent doses of NO, it was observed that SNOPC-6 generated a rapid and significantly greater reduction in blood pressure (∼60% reduction compared to saline) whereas GSNO and SNOPC-2 only achieved a 30–35% decrease. The reduction in blood pressure was transient and recovered to baseline levels within ∼2 min for all compounds. NOx species were transiently elevated (over 5 min) in the plasma, lung, heart and liver. Interestingly, a size-dependent phytochelatin accumulation was observed in several tissues including the heart, lungs, kidney, brain and liver. Biodistribution profiles of NOx were also obtained after i.n. administration, showing significant lung retention of NOx over 15 min with minor systemic increases observed from 5 to 15 min. In summary, this study has revealed interesting in vivo pharmacological properties of SNOPCs, with regard to their dramatic hypotensive effects and differing biodistribution patterns following two different routes of administration.